All-Trans-Retinoic Acid Suppresses Neointimal Hyperplasia and Inhibits Vascular Smooth Muscle Cell Proliferation and Migration via Activation of AMPK Signaling Pathway - Zhang, Jingzhi; Deng, Bo; Jiang, Xiaoli; Cai, Min; Liu, Ningning; Zhang, Shuangwei; Tan, Yongzhen; Huang, Guiqiong; Jin, Wen; Liu, Bin; Liu, Shiming (Frontiers in Pharmacology, 2019)
The proliferation of vascular smooth muscle cell (VSMC) is extensively involved in pathogenesis of neointimal hyperplasia. All-Trans-Retinoic Acid (ATRA) is a natural metabolite of vitamin A. Here, we investigated the involvement of AMP-activated protein kinase (AMPK) in the anti-neointimal hyperplasia actions of ATRA. In this study, we found treatment with ATRA significantly reduced neointimal hyperplasia in left common carotid artery ligation mice model. Accordingly, we found that ATRA reduced the cell proliferation of A7r5, a rat VSMC cell line in a dose- and time-dependent manner. Our results also demonstrated that ATRA altered the expression of proliferation-related proteins, including CyclinD1, CyclinD3 and CDK4 in A7r5 cells. ATRA dose-dependently enhanced the phosphorylation level of AMPKα (Thr172) in the left common carotid artery of model mice. Also, the phosphorylation level of AMPKα in A7r5 was significantly increased in a dose- and time-independent manner. In addition, ATRA dose-dependently reduced the phosphorylation levels of mTOR and mTOR target proteins p70 S6 kinase (p70S6K) and 4E-binding protein 1 (4EBP1). Notably, inhibition of AMPKα by AMPK inhibitor (Compound C) negated the protective effect of ATRA on VSMC proliferation. Molecular docking showed that ATRA could dock into agonist binding site of AMPK, and the binding energy between AMPK and ATRA was -7.91 kcal/mol. Molecular dynamics simulations showed that the binding of AMPK-ATRA was stable. These data demonstrated that ATRA might inhibit neointimal hyperplasia and VSMC proliferation by direct activation of AMPK and inhibition of mTOR signaling.